Impact of Materials on Society - Acord, Sophia Krzys; Jones, Kevin S.; Bryant, Marsha (Open textbook library., 2021)
This textbook supports the Impact of Materials on Society course and teaching materials, developed with the Materials Research Society. The textbook offers an exploration into materials (including ceramics, clay, concrete, glass, metals, and polymers) and the relationship with technologies and social structures. The textbook was developed by an interdisciplinary team from Engineering and Liberal Arts and Sciences, including anthropologists, sociologists, historians, media studies experts, Classicists, and more.